2020
DOI: 10.3390/genes12010008
|View full text |Cite
|
Sign up to set email alerts
|

Novel Advances in Modifying BMPR2 Signaling in PAH

Abstract: Pulmonary Arterial Hypertension (PAH) is a disease of the pulmonary arteries, that is characterized by progressive narrowing of the pulmonary arterial lumen and increased pulmonary vascular resistance, ultimately leading to right ventricular dysfunction, heart failure and premature death. Current treatments mainly target pulmonary vasodilation and leave the progressive vascular remodeling unchecked resulting in persistent high morbidity and mortality in PAH even with treatment. Therefore, novel therapeutic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…In PAH, recent evidence indicates a signaling imbalance between the two principal canonical pathways, with underactive SMAD1/5/8 signaling occurring alongside overactive SMAD2/3 signaling in pulmonary arterial ECs and SMCs ( 13 ). In the remaining sections, we describe how this SMAD signaling imbalance influences the exuberant cell proliferation underlying vascular remodeling and describe therapeutic approaches for either attenuating excessive SMAD2/3 signaling or restoring deficient SMAD1/5/8 signaling in diseased pulmonary vasculature ( 14 20 ). The potential involvement of non-canonical TGF-β superfamily pathways in PAH pathogenesis is poorly understood, but these signaling mechanisms have been implicated in related pathological conditions, such as fibrosis, and merit further study.…”
Section: Tgf-β Superfamily Dysregulation Is a Critical Component Of Pahmentioning
confidence: 99%
“…In PAH, recent evidence indicates a signaling imbalance between the two principal canonical pathways, with underactive SMAD1/5/8 signaling occurring alongside overactive SMAD2/3 signaling in pulmonary arterial ECs and SMCs ( 13 ). In the remaining sections, we describe how this SMAD signaling imbalance influences the exuberant cell proliferation underlying vascular remodeling and describe therapeutic approaches for either attenuating excessive SMAD2/3 signaling or restoring deficient SMAD1/5/8 signaling in diseased pulmonary vasculature ( 14 20 ). The potential involvement of non-canonical TGF-β superfamily pathways in PAH pathogenesis is poorly understood, but these signaling mechanisms have been implicated in related pathological conditions, such as fibrosis, and merit further study.…”
Section: Tgf-β Superfamily Dysregulation Is a Critical Component Of Pahmentioning
confidence: 99%
“…Yet how BMPR2 expression and signaling is regulated remains largely unclear, especially in non-genetic forms. Previously, we and others have shown that targeting BMPR2 signaling and improving the BMPR2/TGF-β disbalance might be an effective therapeutic option for PAH [1][2][3]. Increasing BMPR2 signaling and expression using the repurposed drugs FK506 [4,5] and Enzastaurin [6] has proven to be a successful approach in improving experimental PAH.…”
Section: To the Editormentioning
confidence: 99%
“…Existing drugs do not reduce the progression of vascular remodeling, and patients deteriorate over time. Fewer than 60% of patients survive more than five years after diagnosis (Dannewitz Prosseda et al 2020 ) and lung transplantation remains the only cure (Sommer et al 2021 ). Since PAH therapeutics have had limited efficacy in reversing the pathological mechanisms that drive vascular remodeling, there is a need for more research into the pathology and crosstalk between biochemical and mechanosensitive signaling pathways in pulmonary arterial cells (Sitbon et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%